Does the Unemployment Benefit Institution Affect the Productivity of Workers? Evidence from the Field - Blanco, Mariana; Dalton, Patricio S.; Vargas, Juan F. (Management Science, 2017)
This paper studies the effects of unemployment benefit schemes on individual productivity. We created employment and unemployment in the field and compared workers’ productivity under no unemployment benefits to productivity under two different unemployment schemes. In one scheme, the unemployed received an unconditional monetary transfer. In the other, the monetary transfer was obtained conditional on the unemployed spending some time on an ancillary activity. Our results challenge the standard economic theory prediction that unemployment benefits, especially unconditional compensations, hinder workers’ effort. We find that workers employed under the unconditional scheme are more productive than workers under the conditional one, and both schemes make workers more productive than having no unemployment benefit. We discuss two possible explanations for our results based on reciprocity and differential psychological costs of unemployment across unemployment benefit schemes. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2016.2511 . This paper was accepted by John List, behavioral economics.